IMPACT OF MALOCCLUSIONS ONTO TONGUE MOTION IN PATIENTS WITH NEUROLOGICAL IMPAIRMENTS - A.V. Tsyganok; N.V. Bereziy; V.M. Novikov (Український стоматологічний альманах)
Abstract. Polyetiology of the tongue movement disorders are widely demonstrated in various scientific publications. At the same time the cause of such disorders is often falls within the competence of multiple medical specialties, i.e., rheumatologists, oncologists, endocrinologists, traumatologists, dentists, etc. Data concerning to neurological etiological factors are limited. Mobile component of the pathology has not been fully elucidated. Currently, the tongue movement disorders remain unstudied and issues of its diagnosis and therapy have not been fully demonstrated in scientific publications. The aim of the study is to define the degree of impact of malocclusions onto tongue movement disorders.